Modifications to the delivery of a gross anatomy course during the COVID-19 pandemic at a Mexican medical school - Muñoz Leija, Milton A.; Zarate Garza, Pablo Patricio; Jacobo Baca, Guillermo; Quiroga Garza, Alejandro; Salinas Álvarez, Yolanda; Martínez Garza, Javier Humberto; Elizondo Omaña, Rodrigo Enrique; Guzmán López, Santos (Sociedad Anatómica Española, 2020)
The Coronavirus disease was declared a pandemic this year, causing an impact on medical education. Following the World Health Organization’s (WHO) recommendations, Universities around the world implemented social distancing and the use of online platforms. Anatomists lead medical students, most of which are part of Generation Z. Different technological tools have been used in the gross anatomy course in combination with face-toface classes, but now are forced to move exclusively online. The Human Anatomy Department in the Medical School of the Universidad Autonoma de Nuevo León (UANL) implemented asynchronous sessions as a short-term resolution, transformed to synchronous sessions as the pandemic progressed. It is important to consider the adaptability of the student, the near-peer teacher, and academic staff, with the creation of innovative ideas to facilitate the learning for the student and to maintain the quality of the course. Their role in this modality should be assessed, as it may change medical education and the way to teach in the future for the new generation of medical students. Professors’ roles are changing and it is necessary to adapt to new situations.